THE ROLE OF VIRTUAL AND AUGMENTED REALITY TECHNOLOGIES IN THE DIGITAL ECONOMY - Khusanboeva Tursunoy Mukhammadkasimdzhanovna (Ecominds Press, 2025)
The article analyzes the role of virtual reality (VR) and augmented reality (AR) technologies in the development of the digital economy. Key areas of VR/AR application in industry, education, healthcare and retail are considered. Particular attention is paid to their contribution to improving the efficiency of business processes, reducing costs and creating new forms of interaction with consumers. It is noted that VR/AR technologies are becoming an important element of digital transformation, contributing to the formation of new markets and business models. Further growth of their importance in the digital economy is predicted.
Keywords: Virtual reality (VR), augmented reality (AR), extended reality (XR) technologies, digital economy, innovation, digital transformation.